Antimicrobial resistance and virulence associated genes in Campylobacter jejuni isolated from chicken in Côte d’Ivoire - Bernadette G Goualié; Eric E Akpa; Solange E Kakou-N’Gazoa; Honoré G Ouattara; Sébastien L Niamke; Mireille Dosso (Journal of Infection in Developing Countries)
Introduction: Campylobacter jejuni is one of the major causes of gastroenteritis worldwide of the last century. The aim of this study was to investigate the antibiotics profiles and the virulence gene in C. jejuni strains isolated from chicken in Côte d’Ivoire.